L’etnografo e il narratore - Capello, Carlo (Filosofia, 2020)
Walter Benjamin is a perfect interlocutor for cultural anthropology, which has often taken inspiration from his thought to widen its critical stance. In particular, in this article I aim to show the affinities between the figure of the storyteller, as described in Benjamin’s famous essay on Leskov, and the ethnographer. In the first part of the article, I argue that ethnography is one of the main heirs of Benjamin’s “art of storytelling”, sharing with the latter the dialogical roots, the handcraft nature and the moral dimensions. To this aim, in the last part of the article I present and discuss the works of Lila Abu-Lughod, Steven Caton and Stefania Pandolfo, whose narrative and experimental forms testify clearly the deep assonances between ethnography and Benjamin’s thought.